2018
DOI: 10.1186/s12958-018-0434-y
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and fertility: the influence of stress and quality of life on female fertility

Abstract: There is growing evidence that lifestyle choices account for the overall quality of health and life (QoL) reflecting many potential lifestyle risks widely associated with alterations of the reproductive function up to the infertility. This review aims to summarize in a critical fashion the current knowledge about the potential effects of stress and QoL on female reproductive function. A specific literature search up to August 2017 was performed in IBSS, SocINDEX, Institute for Scientific Information, PubMed, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 110 publications
(106 reference statements)
1
73
0
19
Order By: Relevance
“…2 Among various causes of DOR, psychological factors have emerged as an important one in recent years. [3][4][5] While acute or brief stressors only cause limited damage to women's fertility, chronic stressors can be detrimental to ovarian reserve, leading to adverse fertility outcomes. 4,6 Our previous animal study also indicated that chronic unpredictable stress (CUS) can induce a typical and long-lasting DOR phenotype in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among various causes of DOR, psychological factors have emerged as an important one in recent years. [3][4][5] While acute or brief stressors only cause limited damage to women's fertility, chronic stressors can be detrimental to ovarian reserve, leading to adverse fertility outcomes. 4,6 Our previous animal study also indicated that chronic unpredictable stress (CUS) can induce a typical and long-lasting DOR phenotype in C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%
“…In an extensive literature survey on the potential effects of stress on female fertility, Palomba and co-researchers 19 found that though it is difficult to unravel a cause effect relationship between stress and female fecundity, a strong correlation exists between measures of quality of life, stress, and reproductive function, more specifically in women who are experiencing problems of infertility.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3 ] The diagnostic and therapeutic modalities of infertility assessments currently include many forms of artificial insemination and also pharmacologic and dietary treatments. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%